Successive distinct high‐grade gliomas in L‐2‐hydroxyglutaric aciduria. Issue 2 (23rd October 2014) - Patay, Zoltan; Orr, Brent A.; Shulkin, Barry L.; Hwang, Scott N.; Ying, Yuan; Broniscer, Alberto; Boop, Frederick A.; Ellison, David W.
Abstract: Patients with L‐2‐hydroxyglutaric aciduria are at risk for developing cerebral neoplasms, particularly gliomas, as one of the optical isomers of the known oncometabolite, 2‐hydroxyglutarate is produced in L‐2‐hydroxyglutaric aciduria. To illustrate the concept of sustained oncogenic potential in permanent exposure to L‐2‐hydroxyglutarate in brain tissue, we present the medical history of a patient with L‐2‐hydroxyglutaric aciduria who underwent surgery to remove a right temporal anaplastic astrocytoma and developed an anatomically distinct, but histopathologically similar, tumor in the left frontal region 40 months later. This is the first reported case of successive distinct gliomas in a patient with L‐2‐hydroxyglutaric aciduria. While this implies a significant, cumulative lifetime risk for cerebral neoplasms in patients with this rare organic aciduria, it also allows further insight into a unique mechanism of tumorigenesis in the brain.